1997
DOI: 10.1099/00221287-143-8-2627
|View full text |Cite
|
Sign up to set email alerts
|

The Sch9 protein kinase in the yeast Saccharomyces cerevisiae controls cAPK activity and is required for nitrogen activation of the fermentable-growth-medium-induced (FGM) pathway

Abstract: In cells of the yeast Sacchammyces cerevisiae, trehalase activation, repression of CTTl (catalase), SSA3 (Hsp7O) and other STRE-controlled genes, feedback inhibition of CAMP synthesis and to some extent induction of ribosomal protein genes is controlled by the Ras-adenylate cyclase pathway and by the fermentable-growth-medium-induced pathway (FGM pathway). When derepressed cells are shifted from a non-fermentable carbon source to glucose, the Ras-adenylate cyclase pathway is transiently activated while the FGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 49 publications
7
133
0
Order By: Relevance
“…In the nucleolus, Fhl1 and Ifh1 were proposed to have additional functions, such as repressing rRNA transcription, which would provide an interesting link between rRNA and RP synthesis. Different studies indicated that Sch9 should be involved in the regulation of RP and Ribi gene expression and it was proposed that this protein kinase could be the effector allowing for TORC1 control independent of Fhl1 and Sfp1 (Crauwels et al 1997a;Jorgensen et al 2004;Roosen et al 2005; see also below). Another protein involved in TORC1-mediated transcriptional control of ribosome biosynthesis is Hmo1.…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 99%
See 3 more Smart Citations
“…In the nucleolus, Fhl1 and Ifh1 were proposed to have additional functions, such as repressing rRNA transcription, which would provide an interesting link between rRNA and RP synthesis. Different studies indicated that Sch9 should be involved in the regulation of RP and Ribi gene expression and it was proposed that this protein kinase could be the effector allowing for TORC1 control independent of Fhl1 and Sfp1 (Crauwels et al 1997a;Jorgensen et al 2004;Roosen et al 2005; see also below). Another protein involved in TORC1-mediated transcriptional control of ribosome biosynthesis is Hmo1.…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 99%
“…Subsequently, Sch9 was reported to be essential for the proper nutritional regulation of PKA-dependent phenotypes in glucose-repressed cells, such as the activation of trehalase, the repression of stress response genes and the induction of ribosomal protein genes (Crauwels et al 1997a). These findings led to the concept of the socalled Fermentable Growth Medium (FGM) pathway that is believed to ensure the maintenance of PKA-dependent phenotypes of yeast cells growing on medium containing a rapidly fermented sugar and all essential nutrients, after the transient activation of the cAMP-PKA pathway that occurs during lag phase when cells prepare themselves for fermentative growth (Thevelein 1994;Crauwels et al 1997a). As the FGM pathway appeared to operate independent of cAMP, it was postulated that Sch9 could control the activity of PKA at the level of the free catalytic Tpk subunits (Thevelein 1994;Crauwels et al 1997a).…”
Section: The Protein Kinase Sch9mentioning
confidence: 99%
See 2 more Smart Citations
“…SCH9 encodes a serine͞threonine protein kinase. It is required for the nitrogen activation of the fermentable growth median-induced pathway (18). Because the sch9-delete mutant has a longer nondividing life span than the wild type (17), this brings out a likely association between the efficient usage of the urea cycle and longevity physiology.…”
Section: Longevitymentioning
confidence: 99%